HSV encephalitis after successful minimally invasive debridement for infected pancreatic necrosis: A case of rare central nervous system complication. (March 2021) - Lu, Bei; Cai, Yang; Yin, Junjie; Wang, Jingrui; Jia, Zhong; Hu, Wei; Fang, Jianhua
Patients with acute pancreatitis (AP) often suffer tough complications, some of which are fatal. The early diagnosis and definite treatment of central nervous system (CNS) complications have not been fully achieved yet, which seriously affects the mortality of severe acute pancreatitis (SAP). We present a case of infected pancreatic necrosis (IPN) in a 62-year Chinese man who developed acute herpes simplex encephalitis (HSE) caused by herpes simplex virus type 1 (HSV-1) after favorable minimally invasive retroperitoneal approaches (MIRAs). The patient was successfully treated with 115 days stayed in our hospital. The MIRAs included image-guided retroperitoneal percutaneous catheter drainage (PCD), nephroscopic pancreatic necrosectomy (NPN), and ultrasonic pneumatic lithotripsy system (UPLS) assisted non-narcotic sinus track necrosectomy (NSN). HSE is relatively rare and potentially life threatening. We attempt to discuss the probable risk factors and how the relatively rare HSE are related to the patients of SAP with latent HSV.